Disipasi Energi Pada Kolom Dijacketing Dengan Wire Mesh dan Self Compacting Concrete Akibat Beban Siklik - Hence Michael Wuaten (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2022)
In structures located in earthquake-prone parts, energy dissipation capacity is one of the criteria that must be achieved by the structure. For old structures or built long before earthquake regulations were introduced, it becomes very vulnerable to earthquakes, so it necessitates to be anticipated to prevent collapse, and one method that can be done is by jacketing. In this subject field, testing was conducted using a cyclic load on a reinforced concrete square column measuring 300 mm x 300 mm, which jacketing using wire mesh and self-compacting concrete. From the test results, it was found that in specimens jacketed with M6 wire mesh and self-compacting concrete experienced an increase in accumulative energy dissipation by 23.32% with a relatively minor loss of strength.